Influence of polyols and bulking agents on flavour release from low-viscosity solutions - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert, Ute; Büttner, Andrea; Bader, Stephanie (Food Chemistry, 2011)
The release of four volatile flavour compounds (cis-3-hexen-1-ol, benzaldehyde, ethyl butanoate and butyl isovalerate) from pure water and various low-viscosity aqueous solutions (sucrose, maltitol, erythritol, polydextrose and oligofructose, each at 20% (w/w)) was investigated. Dynamic headspace concentrations of the flavour compounds at thermodynamic equilibrium were monitored by proton-transfer-reaction mass spectrometry (PTR-MS). The rheological properties of the solutions were characterised by their viscosity. Flavour release from pure water increased with increasing hydrophobicity and volatility of the flavour compounds. The highly volatile compounds were retained more extensively in the presence of sucrose, polyols and bulking agents, compared to in pure water, whereas an increase in the release of the less volatile cis-3-hexen-1-ol was observed. All aqueous solutions had similar viscosities, although bulking agent solutions tended to have higher viscosities than polyol solutions of the same concentration. A correlation between viscosity and flavour release in the low-viscosity solutions was not evident. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bulking agent; Flavour release; Polyol; Viscosity; PTR-MS